Whole Brain Mapping of Long-Range Direct Input to Glutamatergic and GABAergic Neurons in Motor Cortex - Luo, Pan; Li, Anan; Zheng, Yanxiao; Han, Yutong; Tian, Jiaojiao; Xu, Zhengchao; Gong, Hui; Li, Xiangning (Frontiers in Neuroanatomy, 2019)
Long-range neuronal circuits play an important role in motor and sensory information processing. Determining direct synaptic inputs of excited and inhibited neurons is important for understanding circuit mechanisms involved in regulating movement. Here, we used monosynaptic rabies tracing technique combined with fluorescent micro-optical sectional tomography to characterize the brain-wide input to motor cortex. The whole brain dataset showed that main excited and inhibited neurons in the motor cortex receive inputs from similar brain regions with quantitative difference. With 3D reconstruction, we found that the distribution of input neurons that target the primary and secondary motor cortex had different patterns. In cortex, the neurons projecting to primary motor cortex mainly distributed in the lateral and anterior portion, while those to secondary motor cortex distributed in the medial and posterior portion. The input neurons in subcortical areas also showed the topographic shift model, as in thalamus the neurons distributed as outer and inner shells and the neurons in claustrum and amygdala were in ventral and dorsal part respectively. These results lay the anatomical foundation for understanding the organized pattern of motor circuits and the functional differences between primary and secondary motor cortex.